Chemical characterization of polyethylene geomembranes by chromatography coupled to mass spectrometry using multivariate tools. (May 2022) - Valentin, Leonardo Antonio; Valentin, Clever Aparecido; Kobelnik, Marcelo; Lins da Silva, Jefferson
Abstract: Geomembrane is a type of material used in civil engineering and environmental engineering works for the protection and recovery of the environment. Five geomembranes commercially obtained from three Brazilian companies were chemically characterized. The Gas Chromatography-Mass Spectrometry (GC-MS) technique was used to determine and identify the compounds Semivolatile Organic Compounds (SVOCs) and Volatile Organic Compounds (VOCs) based on their mass and spectrum (fragmentation) in order to characterize the materials and multivariate analysis tools were applied. Moreover, 211 compounds were selected for SVOCs and 59 compounds for VOCs. Considering the 211 compounds, 159 met the p-value criterion <0.05. For the 159 compounds, 130 met the cut-off criterion of 2.0 for the fold change analysis and were considered in the study. Regarding VOC compounds, from the 59 compounds considered, 25 met the p-value criteria <0.05 and 15 for the cut-off 2.0 criteria for fold change analysis. The combination of chromatographic determination with multivariate analysis was applied and showed to be an excellent tool for chemical characterization and the differentiation between the five groups can be observed. This information can be useful for these techniques in routines for material quality control and for geosynthetics databases.